Pengembangan Sensor Kimia Berbasis Strip Tes untuk Deteksi Logam Berat Merkuri pada Sampel Produk Jamu - Rizqi Amaliyah; Nia Kristiningrum; Indah Purnama Sary (UPT Percetakan dan Penerbitan Universitas Jember, 2021)
The use of plants as a traditional medicine in the modern era is still in high demand. One of the herbs commonly used by Indonesian is analgesic herbal medicine. The safety aspect of herbal medicine should be considered, such as heavy metal contamination. Mercury is the typical heavy metal found in polluting herbal plants. The maximum mercury level allowed in a medicinal preparation has been regulated by BPOM RI, as much as ≤ 0.5 ppm. A high level of mercury contamination causing toxic effects on the body due to protein precipitation, which inhibits enzyme activity and acts as a corrosive material. A technology that allows the detection of mercury is a chemical sensor. The strip test is optimal if the reagent 1-(2-thiazolyl azo)-2-naphthol (TAN) concentration at 1000 ppm and the sample has been confirmed at pH 7. The results of the strip test characterization showed that the response time was in the range of minutes 17 to 24, the use time of the test strips for 28 days if stored in room temperature and 29 days if stored at in refrigerator temperature, linearity with r = 0.998, Vx0 = 3.96%, p-value = 0.00000172, LOD = 0.102 ppm and LOQ = 0.306 ppm, interference value <5%, precision with RSD 6.54%, and accuracy with the value of % recovery 98.007%. T-test analysis showed p= 0.872, meaning no significant difference between the application of TAN-based test strips with the ICP-AES method.